(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this writing is to find out the problems related to how the regulations are related to insurance and how protection is related to policyholders from insurance companies that are unable to pay for one of the products in the agreement. This writing discusses the basic arrangements related to insurance and legal protection for policyholders, especially victims of default in term savings insurance products. The achievement of legal certainty is supported by the existence of statutory regulations no. 21 of 2011 concerning the Financial Services Authority no. 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector. Given that insurance policy holders are generally individuals, a number of laws and regulations pay more attention and legal protection to insurance policy holders.